Jaime Meek: capstone - Meek, Jaime, artist (Colorado State University. Libraries, 2014)
The artist's statement: My work is directed toward generating clear, energetic, and invigorating ideas through unique, fresh, and creative design concepts. Art for me has always been a communication tool. Design has the capability of reaching a wider audience, and making a resounding impact conveying a message or an idea being. Graphic Design allows me to use my skills as an artist to convey ideas in an abstract, captivating manner. I am always aspiring to grow as an artist and expand my skills as a Graphic Designer. My goal as an artist is to create a channel of communication through successful visuals that relay a message in the same or better sense that words can. I enjoy working mostly with ink, graphite, colored pencil, permanent marker, and watercolor. The process always varies. Painting was my beginning point as an artist. Through the course of time and education I have come to love many other media, particularly drawing and photography. Recently, I have been trying to implement my physical artistic skills into my graphic design work. As a designer in the 21st century, it is very easy to get caught up in working solely with computer generated tools. Graphic Designers such as Gitte Kathe have inspired me in a new design process that I plan on integrating into future creations. I plan on exploring the realm outside of the digital age and bringing aspects of physical art into my graphic design creations. The process of my design work begins with word play. Examining the project at hand, I write down the words that stand out visually in my mind. From there, I research the topics and save images that I find enticing and powerful. Next, I create and gather photos, sketches, drawings, and any other source of visual inspiration that can help mold the visual content I want to use in my work. From there, the media is applied on the computer where the use of typography and layout are applied to create an aesthetically captivating product. When trying to capture a certain emotion or feeling in an artwork, I try to place myself in an environment that stimulates that emotion. This can be done by environment, music, and people. By doing this the message and the idea that I am trying to get across can really resonate with me. I'm am an expert in my processes, and wish to share it through the experience of my design work.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.